Representasi Korban Perdagangan Manusia dalam Novel Re: dan Perempuan karya Maman Suherman - Ridho'i, Sekar Tiara Sukma; Dewi, Putri Aisyiyah Rachma (The Commercium, 2024)
This research focuses on how human trafficking victims are represented in the novel Re: dan Perempuan by Maman Suherman using Semiotic Analysis by Ferdinand de Saussure, the paradigmatic and the syntagmatic one. Human trafficking is one of the most violent crime in the world according to the United Nation, so it requires special attention especially towards its victims. This case often becomes a topic in literary works, one of them is Re: dan Perempuan, which tells the story of a sexual exploitation victims. This research uses a qualitative interpretive approach, with literature review as its data collection technique and the novel Re: dan Perempuan is the primary source of this research. The aim of this study is to understand of how human trafficking victims are represented in the novel and it through the point of psychographic of the victims and the treatment received by the victims. From this research, there are found 6 narratives that explain about the psychographic of the victims and 9 narrative of the treatment received by the victims. The psychographic of the victims are depicted as someone who wears a heavy make up, indicating that the victims represented as a minors that is wearing inappropriate clothes who some of them are wearing make up and some are not. And mentally, the human trafficking victims are represented as someone with low self-esteem. On the other hand, the v treatment received is found to include threats, violence, extortion, slavery, and even murder.